The Role of Parents on the Care of Tolls during the Covid-19 Pandemic - Dewi Modjo; Andi Akifa Sudirman; Riskawaty Nuna; Mutya Datungsolang; Suparjo A. Nasibu (Journal of Universal Community Empowerment Provision, 2021)
Toddlers are one of the age groups that are vulnerable to being infected with Covid-19, a disease caused by the SARS-Cov 2 Virus which has become a global pandemic since March 2020. The age limit for toddlers is 1-3 years (toddlers) and 3-5 years (pre-school). Therefore, the care of toddlers during the COVID-19 pandemic must be adjusted to the health protocols set by the government to break the chain of transmission. This is the goal of community service activities, namely to increase parents' knowledge by conducting counseling on how "The Role of Parents in Caring for Toddlers During the Covid 19 Pandemic". The method used is education using Power Points, Banners and Leaflets about caring for toddlers during the Covid 19 pandemic. The results of this activity achieved good results because as many as 21 mothers of toddlers were willing to take part in counseling and willing to help implement clean and healthy living behaviors and ways prevent and overcome the spread of Covid 19. Conclusion: a more intensive relationship between parents and their children, which has an impact on the growth and development of children, including how to treat children under five years of age during the Covid 19 pandemic. So that, Parents are the main protectors for their children's health